Water and sediment pesticide contamination on indigenous lands surrounded by oil palm plantations in the Brazilian Amazon - Damiani, Sandra (2023)
Large-scale oil palm cultivation with intensive pesticide use has been growing worldwide and reached the Brazilian Amazon. The rapid expansion of this crop over the last decade has reached vast areas, including the boundaries of different indigenous lands. This study aimed at assessing the occurrence of pesticide residues in surface and ground waters as well as drainage sediments in the Tur´e-Mariquita Indigenous Territory, in addition to other nearby indigenous villages in the northeastern state of Par´ a. Thirty-three (33) water samples were collected from streams, springs and from active and abandoned wells at 19 sampling points, as well as 16 sediment samples at 9 sampling sites both during dry and rainy seasons. In total, 49 environmental samples were taken during fieldworks and subsequently analyzed by means of liquid chromatography and mass-mass spectrometry. The analytical determination of pesticide residues showed the occurrence of three pesticides in the water both from streams and from wells, two of them knowingly used by the oil palm company: glyphosate-based herbicides (GBHs) and endosulfan insecticides. Although the highest glyphosate and endosulfan levels as well as the maximum concentration of glyphosate found in ground water are within the Brazilian environmental regulatory guidelines, all the values for human consumption found in the glyphosate-containing samples are well above the European Union regulatory standards. Our results draw the attention to the risks of biota contamination and human exposure to multiple-pesticide residues.